Left ventricular systolic function and diastolic filling after intermittent high intensity team sports. Issue 4 (23rd July 2004) - George, K P; Dawson, E; Shave, R E; Whyte, G; Jones, M; Hare, E; Gaze, D; Collinson, P
Abstract : Background: Prolonged steady state exercise can lead to a decrease in left ventricular (LV) function as well as promote the release of cardiac troponin T (cTnT). There is limited information on the effect of intermittent high intensity exercise of moderate duration. Objectives: To determine the effect of intermittent high intensity exercise of moderate duration on LV function. Methods: Nineteen male rugby and football players (mean (SD) age 21 (2) years) volunteered. Assessments, before, immediately after, and 24 hours after competitive games, included body mass, heart rate (HR), and systolic blood pressure (sBP) as well as echocardiography to assess stroke volume (SV), ejection fraction (EF), systolic blood pressure/end systolic volume ratio (sBP/ESV), and global diastolic filling (E:A) as well as to indirectly quantify preload (LV internal dimension at end diastole (LVIDd)). Serum cTnT was analysed using a 3rd generation assay. Changes in LV function were analysed by repeated measures analysis of variance. cTnT data are presented descriptively. Results: SV (91 (26) v 91 (36) v 90 (35) ml before, after, and 24 hours after the game respectively), EF (71 (8) v 70 (9) v 71 (7)%), and sBP/ESV (4.2 (1.8) v 3.8 (1.9) v 4.1 (1.6) mm Hg/ml) were not significantly altered (p>0.05). Interestingly, whereas LVIDd was maintained after the game (50 (5) v 50 (6) mm), sBP was transiently but significantly reduced (131 (3) v 122 (3) mm Hg; p<0.05). E:A was moderately (p<0.05) reduced after the game (2.0 (0.4) v 1.5 (0.4)) but returned to baseline within 24 hours. No blood sample contained detectable levels of cTnT. Conclusions: In this cohort, LV systolic function was not significantly altered after intermittent activity. A transient depression in global diastolic filling was partially attributable to a raised HR and could not be explained by myocyte disruption as represented by cTnT release.